One step geometrical calibration method for optical coherence tomography. (1st December 2015) - Díaz, Jesús Díaz; Stritzel, Jenny; Rahlves, Maik; Majdani, Omid; Reithmeier, Eduard; Ortmaier, Tobias; Roth, Bernhard
Abstract: We present a novel one-step calibration methodology for geometrical distortion correction for optical coherence tomography (OCT). A calibration standard especially designed for OCT is introduced, which consists of an array of inverse pyramidal structures. The use of multiple landmarks situated on four different height levels on the pyramids allow performing a 3D geometrical calibration. The calibration procedure itself is based on a parametric model of the OCT beam propagation. It is validated by experimental results and enables the reduction of systematic errors by more than one order of magnitude. In future, our results can improve OCT image reconstruction and interpretation for medical applications such as real time monitoring of surgery.